Combined deficiency of alpha and epsilon sarcoglycan disrupts the cardiac dystrophin complex - Lancioni, Alessio (Oxford University Press, 2011)
Cardiomyopathy is a puzzling complication in addition to skeletal muscle pathology for patients with mutations in β-, γ- or δ-sarcoglycan (SG) genes. Patients with mutations in α-SG rarely have associated cardiomyopathy, or their cardiac pathology is very mild. We hypothesize that a fifth SG, ɛ-SG, may compensate for α-SG deficiency in the heart. To investigate the function of ɛ-SG in striated muscle, we generated an Sgce-null mouse and a Sgca-;Sgce-null mouse, which lacks both α- and ɛ-SGs. While Sgce-null mice showed a wild-type phenotype, with no signs of muscular dystrophy or heart disease, the Sgca-;Sgce-null mouse developed a progressive muscular dystrophy and a more anticipated and severe cardiomyopathy. It shows a complete loss of residual SGs and a strong reduction in both dystrophin and dystroglycan. Our data indicate that ɛ-SG is important in preventing cardiomyopathy in α-SG deficiency.